2001
DOI: 10.1051/0004-6361:20010701
|View full text |Cite
|
Sign up to set email alerts
|

Relationship in sign between tilt and twist in active region magnetic fields

Abstract: Abstract.In this paper, we analyze the photospheric vector magnetograms of 286 active regions (ARs) which were observed from 1988−1996 during the 22nd solar cycle at Huairou Solar Observing Station in Beijing. Among these active regions, which are dominated by bipolar magnetic fields, 203 ARs exhibit a simple configuration of magnetic fields, while 83 ARs show a more complicated configuration of magnetic fields. When we explore the relationship between the sign of the tilt angle of magnetic polarity axis and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 35 publications
(48 reference statements)
1
25
1
Order By: Relevance
“…They conclude that a substantial fraction of ARs in their dataset show evidence of having gone through the kink instability. Earlier, Tian et al (2001), using Huairu vector magnetograms of 286 ARs reached an opposite conclusion: they found a positive correlation between tilt and twist (after correcting for their definition of tilt, which results in a sign opposite to that of Holder et al, 2004). As Holder et al (2004) remark, Tian et al (2001) did not take out the mutual latitudinal dependence between twist and tilt, and therefore any signatures of writhing could have been suppressed in their data set.…”
Section: Tilt Anglementioning
confidence: 92%
See 1 more Smart Citation
“…They conclude that a substantial fraction of ARs in their dataset show evidence of having gone through the kink instability. Earlier, Tian et al (2001), using Huairu vector magnetograms of 286 ARs reached an opposite conclusion: they found a positive correlation between tilt and twist (after correcting for their definition of tilt, which results in a sign opposite to that of Holder et al, 2004). As Holder et al (2004) remark, Tian et al (2001) did not take out the mutual latitudinal dependence between twist and tilt, and therefore any signatures of writhing could have been suppressed in their data set.…”
Section: Tilt Anglementioning
confidence: 92%
“…Earlier, Tian et al (2001), using Huairu vector magnetograms of 286 ARs reached an opposite conclusion: they found a positive correlation between tilt and twist (after correcting for their definition of tilt, which results in a sign opposite to that of Holder et al, 2004). As Holder et al (2004) remark, Tian et al (2001) did not take out the mutual latitudinal dependence between twist and tilt, and therefore any signatures of writhing could have been suppressed in their data set. Nandy (2006), further analysing the dataset used by Holder et al (2004), as well as Yang et al (2009), analysed the twist-tilt relationship.…”
Section: Tilt Anglementioning
confidence: 92%
“…So we need other methods to investigate the helicity properties in the solar atmosphere. Recently, many authors have used vector magnetographs to calculate the current helicity h c = μ 0 B z J z (Abramenko et al 1996;Bao & Zhang 1998) or the force-free field parameter α best (Pevtsov et al 1995;Tian et al 2001) of active regions that represent the helicity of the magnetic flux tubes. The shapes of sigmoid coronal loops were also studied (Pevtsov et al 1995;Canfield & Pevtsov 1999;Pevtsov et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Ii is found that more than 80% of the active regions in the northern (southern) hemisphere show negative (positive) sign of current helicity. Tian et al (2001) found that there is a negative correlation between the sign of the tilt angle and the sign of the current helicity if the tilt angle is set a positive value (0-90 • ) in the northern hemisphere and a negative value (0-90 • ) in the southern hemisphere for active regions following Joy's law. Most of the X-ray flares larger than M-class during the 22nd solar cycle have a tendency to locate in some longitudinal bins, where active regions with "abnormal chirality" appear frequently.…”
Section: H Zhangmentioning
confidence: 99%